Leadership 3.0 Based Principal’s Leadership to Improve Teachers’ Work in Multicultural Society - Tukiyo, Joko Nurkamto, Siswandari & Gunarhadi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study aims at describing whether leadership 3.0 based principal’s leadership canimprove teachers’ work in multicultural society. To answer the problem, the writer didliterary study and resuming relevant researches. Leadership implemented by a principalin an education institution (school) influences the teachers’ work. A good principalleadership is able to make the teachers do their assignment and obligation well. A goodpractice done by a principal will be an example of all members of the institution. Tomeet the hope, the writer did a study on leadership 3.0 based principal’s leadershipcovering six aspects, namely physicallity, intellectuality, emotionality, sociability,personability, and moral ability. Based on the study, it was concluded that leadership3.0 based principal’s leadership can improve teachers’ work in multicultural society.Keywords: leadership 3.0 based principal’s leadership, teachers work, multicultural society